2012
DOI: 10.1093/mnras/sts276
|View full text |Cite
|
Sign up to set email alerts
|

Disc clearing of young stellar objects: evidence for fast inside-out dispersal

Abstract: The time-scale over which and the modality by which young stellar objects (YSOs) disperse their circumstellar discs dramatically influences the eventual formation and evolution of planetary systems. By means of extensive radiative transfer (RT) modelling, we have developed a new set of diagnostic diagrams in the infrared colour-colour plane (K -[24] vs. K -[8]), to aid with the classification of the evolutionary stage of YSOs from photometric observations. Our diagrams allow the differentiation of sources wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 81 publications
5
79
0
Order By: Relevance
“…Clarke et al (2001) showed that when the mass accretion rate becomes comparable with the mass loss by photoevaporation, a gap opens at around a few AUs, rapidly shutting down accretion (the so-called UV switch) and producing a transition disc. The outer disc left is quickly eroded from the inside out by photoevaporation, which agrees with observational findings Koepferl et al 2013). While this explains some transition discs, it does not explain all of them.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Clarke et al (2001) showed that when the mass accretion rate becomes comparable with the mass loss by photoevaporation, a gap opens at around a few AUs, rapidly shutting down accretion (the so-called UV switch) and producing a transition disc. The outer disc left is quickly eroded from the inside out by photoevaporation, which agrees with observational findings Koepferl et al 2013). While this explains some transition discs, it does not explain all of them.…”
Section: Introductionsupporting
confidence: 88%
“…This is further reinforced by the fact that the viscous time-scale in the outer regions of protoplan-etary discs ( 100 AU) is Myr, which implies that some other process must drive disc dispersal at these radii. Observations currently show that approximately 10 percent of all observed discs (Kenyon & Hartmann 1995;Koepferl et al 2013) are "transition" discs (TD). If all discs go through the transition disc phase, this implies that this phase must be short-lived (of order of 10 5 years), implying that disc evolution observes a "two-time scale behaviour".…”
Section: Introductionmentioning
confidence: 99%
“…If one requires that Jupiter takes a million years to accrete its envelope, then its runaway growth needs to be limited by a stellar accretion rate of 10 −9 M yr −1 . However, at this very low rate, the disk photoevaporates rapidly (i.e., a few 10 5 yr, see, e.g., Koepferl et al 2013;Gorti et al 2009;Szulágyi et al 2012). Thus a Jupiter mass of gas is unlikely to be accreted by the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Luhman et al 2010;Koepferl et al 2013), and it can reproduce the intensities and profiles of emission lines produced in the wind . However, the direct observation of a disc undergoing gap formation via photoevaporation is still lacking.…”
Section: Introductionmentioning
confidence: 99%